The Potential of Umbul Sungsang Spring Water for Drinking Wate, PDAM, and Irigation Purposes at Banyudono, Boyolali, Central Java - Hakim, Rohman; Priyana, Yuli (Universitas Muhammadiyah Surakarta, 2000)
Umbul Sungsang spring located in the foot of a Merapi is on shift zone between volcanic foot plain and fluvial volcanic fott plain constitutes spring belt. Up to the present, the population use that spring for drinking water and irrigation. The planning of taking water by Municipal Waterworks to supply Solo population causes people around it worried because the usually use that spring. Therefore it is needed to conduct a research to know the potential of that spring. The aim of this research is to account how much the need of drinking water, manucipal waterworks and irrigation and the potential of the spring which is available. The research uses survey method. Primary and secondary data are collected, analyzed quantitatively by using software aid to do simulation the need of irrigation. The result of the research shows that the need of drinking water is 0.068 lt/second/day taken in dry season; manucipal waterworks uses 200 lt/second/day and for irrigation is about 442.2 lt/second/day with the pattern rice â tobacco â rice. Irrigation is also supplied from Bendung Bukur Ireng. The result of the research also shows that in October period I, II, III, and November period II and I lack of water. Therefore municipal waterworks must not use water on Otober and November, while on July and September adjust to the rest of discharge of water, which is available. Its water quality fulfils the requirement for various needs.